Early spring (June) field work on the La Pérouse Bay salt marsh, Hudson Bay, Manitoba, Canada. - Bazely, Dawn
Susan (Sue) Cargill and Michelle Kortnaar prepare to rebuild chicken wire exclosures that will exclude grazing lesser snow geese, in the Mast River Delta, La Pérouse Bay, Manitoba, Canada. The exclosures, left up overwinter, were flattened by snow and ice during the melting of the Mast River. This research was carried out by the Robert (Bob) L. Jefferies' herbivory lab group.